FOUR CORNERS DEBATE TOWARD STUDENTS’ SPEAKING SKILL OF THE SECOND SEMESTER AT ENGLISH EDUCATION PROGRAM STKIP PGRI LUBUKLINGGAU - Syaprizal Syaprizal (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
This research is aimed to investigate whether or not there is any significant effect four corners debate toward students speaking skill of the second semester at English education program STKIP PGRI Lubuklinggau. Four Corners Debate is one of an instructional strategy in speaking skill. This strategy can be used to solve students difficult in speaking skill and also can help students active in speaking activates especially in class. The subject of this investigation was all students of second semester. The purposive sampling was used in this investigation. The design of this research is quasi-experimental method. The data were collected by using oral test.  After data were collected, the researcher used t-test analysis to find any significant effect of corner debate toward speaking skill. The result of this research showed that the mean score of pre-test was 65.05 and the mean score of post-test was 77.11. T-test value was 3.90, at the level of significance 0.05 with df 30, the value of t-table was 1.697. It known that t-test value was higher that t-table indicated that the research hypothesis (Ha) was accepted where there was significant effect four corner debate toward students’ speaking skill. In summary, four corner debate strategies can help students more active in using English specially in speaking skill